Early Post-Vaccination Gene Signatures Correlate With the Magnitude and Function of Vaccine-Induced HIV Envelope-Specific Plasma Antibodies in Infant Rhesus Macaques - Vijayan, K. K. Vidya; Cross, Kaitlyn A.; Curtis, Alan D.; Van Rompay, Koen K. A.; Pollara, Justin; Fox, Christopher B.; Tomai, Mark; Hanke, Tomáš; Fouda, Genevieve; Hudgens, Michael G.; Permar, Sallie R.; De Paris, Kristina (Frontiers in Immunology, 2022)
A better understanding of the impact of early innate immune responses after vaccine priming on vaccine-elicited adaptive immune responses could inform rational design for effective HIV vaccines. The current study compared the whole blood molecular immune signatures of a 3M-052-SE adjuvanted HIV Env protein vaccine to a regimen combining the adjuvanted Env protein with simultaneous administration of a modified Vaccinia Ankara vector expressing HIV Env in infant rhesus macaques at days 0, 1, and 3 post vaccine prime. Both vaccines induced a rapid innate response, evident by elevated inflammatory plasma cytokines and altered gene expression. We identified 25 differentially-expressed genes (DEG) on day 1 compared to day 0 in the HIV protein vaccine group. In contrast, in the group that received both the Env protein and the MVA-Env vaccine only two DEG were identified, implying that the MVA-Env modified the innate response to the adjuvanted protein vaccine. By day 3, only three DEG maintained altered expression, indicative of the transient nature of the innate response. The DEG represented immune pathways associated with complement activation, type I interferon and interleukin signaling, pathogen sensing, and induction of adaptive immunity. DEG expression on day 1 was correlated to Env-specific antibody responses, in particular antibody-dependent cytotoxicity responses at week 34, and Env-specific follicular T helper cells. Results from network analysis supported the interaction of DEG and their proteins in B cell activation. These results emphasize that vaccine-induced HIV-specific antibody responses can be optimized through the modulation of the innate response to the vaccine prime.